Kościół św. Jana Ewangelisty w Bralinie. Przyczynek do dziejów ewangelickiej architektury sakralnej na pograniczu śląsko-wielkopolskim - Krzyślak, Bolesława (Ecclesia. Studia z Dziejów Wielkopolski, 2012)
The Evangelicals of Bralin had to wait very long for their own place of prayer - until mid 19th century. Initially they could use a schoolroom and later a room in the town hall. It was only in the years 1866-1867 that a church dedicated to St. John the Evangelist, which today, was built in the market square. It was erected as a brick structure, unplastered (Rohbau), in the so-called arcaded style (Rundbogenstil) according to a unique government design created by Berlin architects with the participation of Friedrich August Stiiler. The polychromy of the interior, which has survived till the present day, comes from 1917 and commemorates the jubilee of the church's 50th anniversary as well as the solemnly celebrated 400th anniversary of the Reformation. Pastor Zenon Bessert was the last permanent administrator of the Evangelical parish in Bralin, after 1920 it passed in the care of ministers from Kępno. The church is an exceptional example of well preserved Evangelical buildings that deserves to be placed under the special care of the conservator of historical architecture.